Amino acid starvation sensing dampens IL-1β production by activating riboclustering and autophagy - Battu, Srikanth; Afroz, Sumbul; Giddaluru, Jeevan; Naz, Saima; Huang, Weishan; Khumukcham, Saratchandra Singh; Khan, Rafiq Ahmad; Bhat, Saleem Yousuf; Qureshi, Insaf Ahmed; Manavathi, Bramanandam; Khan, Aleem Ahmed; August, Avery; et al. (PLoS biology, 2018)
Activation of the amino acid starvation response (AAR) increases lifespan and acute stress resistance as well as regulates inflammation. However, the underlying mechanisms remain unclear. Here, we show that activation of AAR pharmacologically by Halofuginone (HF) significantly inhibits production of the proinflammatory cytokine interleukin 1β (IL-1β) and provides protection from intestinal inflammation in mice. HF inhibits IL-1β through general control nonderepressible 2 kinase (GCN2)-dependent activation of the cytoprotective integrated stress response (ISR) pathway, resulting in rerouting of IL-1β mRNA from translationally active polysomes to inactive ribocluster complexes-such as stress granules (SGs)-via recruitment of RNA-binding proteins (RBPs) T cell-restricted intracellular antigen-1(TIA-1)/TIA-1-related (TIAR), which are further cleared through induction of autophagy. GCN2 ablation resulted in reduced autophagy and SG formation, which is inversely correlated with IL-1β production. Furthermore, HF diminishes inflammasome activation through suppression of reactive oxygen species (ROS) production. Our study unveils a novel mechanism by which IL-1β is regulated by AAR and further suggests that administration of HF might offer an effective therapeutic intervention against inflammatory diseases.